Effect of intra- and interspecific competition on the performance of native and invasive species of Impatiens under varying levels of shade and moisture - Skálová, Hana; Jarošík, Vojtěch; Dvořáčková, Śárka; Pyšek, Petr (PloS one, 2013)
Many alien plants are thought to be invasive because of unique traits and greater phenotypic plasticity relative to resident species. However, many studies of invasive species are unable to quantify the importance of particular traits and phenotypic plasticity in conferring invasive behavior because traits used in comparative studies are often measured in a single environment and by using plants from a single population. To obtain a deeper insight into the role of environmental factors, local differences and competition in plant invasions, we compared species of Impatiens (Balsaminaceae) of different origin and invasion status that occur in central Europe: native I. noli-tangere and three alien species (highly invasive I. glandulifera, less invasive I. parviflora and potentially invasive I. capensis). In two experiments we harvested late-stage reproductive plants to estimate performance. The first experiment quantified how populations differed in performance under varying light and moisture levels in the absence of competition. The second experiment quantified performance across these environments in the presence of intra- and inter-specific competition. The highly invasive I. glandulifera was the strongest competitor, was the tallest and produced the greatest biomass. Small size and high plasticity were characteristic for I. parviflora. This species appeared to be the second strongest competitor, especially under low soil moisture. The performance of I. capensis was within the range of the other Impatiens species studied, but sometimes limited by alien competitors. Our results suggest that invasion success within the genus Impatiens depends on the ability to grow large under a range of environmental conditions, including competition. The invasive species also exhibited greater phenotypic plasticity across environmental conditions than the native species. Finally, the decreased performance of the native I. noli-tangere in competition with other species studied indicates that this species may be possibly excluded from its sites by invading congeners.
Keywords: Phenotype; Impatiens; sluneční záření; životní prostředí; Biomass; ekosystém; zavlečené druhy; Water; fenotyp; Ecosystem; Introduced Species; Sunlight; Environment; biomasa; voda